Analisis Survei Pengelolaan Arsip Unit di Universitas Sanata Dharma Yogyakarta - Rahayuningsih, Fransisca (Universitas Negeri Padang, 2021)
Archives are created in every institution large and small. College is one of the institutions that produces many archives of academic and administrative works. The archives created in universities need to be managed and stored so that they can be traced and utilized by the institution concerned and by other parties who need it. In line with this, Sanata Dharma University (USD) as the bearer of the Tri Dharma of Higher Education seeks to manage archives in all units at the university level. The management of the USD institutional archives is carried out by carrying out the mandate of the 2018-2022 USD RENSTRA, where the initial target for achievement is the 1993-2020 USD archives. Archival managers are expected to be able to collect and archive all USD institutional documents from 1955 s.d. 2020. Records management at the USD level is left to the USD Library.USD Library plans to carry out acquisitions/archive collection of units. This step was preceded by an online survey of records management in units, so that USD Libraries had an initial picture of archive management across all units in USD. This online survey was conducted using qualitative methods. The population in the survey is education staff, both permanent and non-permanent in USD, with a total of 376 people. The sample used in the survey is 76 people, the sample selection using convenience sampling technique.The survey results showed that there were 52 people who filled out the survey. The most types/subjects of archives owned by units in USD are curriculum archives (25 units), lectures (24 units) and student affairs (20 units). The largest media/archive form is print/paper (50 units), but most of the units have been digitized (43 units). Other archival media that are also owned by the unit are photos, souvenirs, compact disks, videos, digital video disks, blueprints, maps and technical drawings. The processing of unit archives in USD varies, both those that have been digitized (33 units), have been inventoried/recorded (25 units), have been numbered/coded (6 units), have been destroyed (2 units) to archives that have not been managed properly ( not yet digitized, not yet inventoried, not yet coded). There are archives that have been arranged in a filing cabinet/rack/file/order box (40 units), archives are organized by year/subject/alphabatic number (26 units). The majority of HR Archive Managers in all units do not have HR that specifically manages archives (48 units). The majority of archive borrowing is no archive loan. The majority of facilities/tools/software for archival tracing do not have facilities/tools/software for archival tracing (47 units). Permits for borrowing archives from units at Sanata Dharma University, the majority allowed borrowing archives (47 units). The majority of data collection/inventory of archive types to be borrowed from units at Sanata Dharma University answered that data collection/archive inventory was carried out by each unit to ensure the completeness and correctness of the archives to be borrowed (26 units). Static Archives Management and Storage at Sanata Dharma University answered that the USD Library only manages and stores digital archives and printed archives are stored in their respective units (29 units). The return of the static archives borrowed for processing by the USD Library, the majority answered that the printed static archives were returned to the unit (28 units).